15, 16-dihydrotanshinone I in Danshen ethanol extract aggravated cholestasis by inhibiting Cyp3a11 mediated bile acids hydroxylation. (15th March 2023) - Li, Yue; Wang, Qian; Jin, Jingyi; Tan, Bo; Ren, Jie; Song, Guochao; Zou, Bin; Weng, Fengyi; Yan, Dongming; Qiu, Furong
Abstract: Our previous study found that high-dose Tanshinones Capsule (TC) aggravated cholestasis in mice. To explore its underlying mechanism, main tanshinones components (15, 16-dihydrotanshinone I (DTI), cryptotanshinone (CTS) and tanshinone IIA (TSA)) form TC were studied separately. Bile acids (BAs) that were primarily metabolized by hydroxylation were identified, and then the inhibitory effect of each tanshinones on their hydroxylation were evaluated. The anti-cholestasis effect of each tanshinones were studied in mice, the hepatic concentrations of BAs and tanshinones were measured and analyzed as well. The effect of tanshinones on Cyp3a11 protein expression was investigated. DTI exhibited inhibitory effect on the hydroxylation of lithocholic acid (LCA), taurolithocholic acid (TLCA) and taurochenodeoxycholic acid (TCDCA), their IC50 values were 0.81, 0.36 and 1.29 μM, respectively. The hydroxylation of LCA, TLCA and TCDCA were mediated by Cyp3a11. Low-dose DTI, CTS and TSA ameliorated cholestatic liver injury in mice, while high-dose DTI didn't exhibit anti-cholestatic effect. The hepatic BAs profiles indicated that hydroxylation of BAs was inhibited in high-dose DTI group. DTI and TSA up-regulated the protein expression of Cyp3a11. As the hepatic concentration of DTI increased, the inhibitory effect at enzymatic activity level overwhelmed its up-regulation effect at protein level, thus resulted in worsening of cholestasis. Highlight: DTI was responsible for the cholestasis caused by high-dose Tanshinones Capsule. Cyp3a11-mediated hydroxylation was detoxification pathway of bile acids in mice. DTI could up-regulate cyp3a11 protein expression in less dose-proportional manner. High concentration of DTI could inhibit the hydroxylation activity of Cyp3a11. Protein up-regulation was overwhelmed by enzyme activity inhibition by high-dose DTI.